PENGARUH PENAMBAHAN AMPAS KELAPA TERHADAP KANDUNGAN NUTRISI PRODUK PANGAN: TINJAUAN SISTEMATIS - Vania Salsabila Anjani, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Coconut dregs are byproducts of coconut milk and coconut oil that are highly nutritious as they contain carbohydrates, protein, and fiber. Despite the high nutritional content, the application of coconut dregs in the food industry is still ineffective. One way to maximize it is to process them to produce flour. This systematic review aims to summarize the addition of coconut dreg flour and its effect on the nutritional content of different types of foods. The study uses the PRISMA guideline to evaluate the articles with databases, including Science Direct, Taylor & Francis, EBSCOhost, and Garuda. This systematic review provides a comprehensive review of 17 articles that focus on the application of coconut dregs in food products and their effect on nutritional content. The result of the systematic review shows that the addition of coconut dreg in food products affects the nutritional content by elevating the overall protein, fiber, and fat content. In addition, the presence of additional ingredients and the processing method of the coconut dreg can highly influence the nutritional content of coconut dreg. Therefore, it is important to pay close attention to these factors to produce a coconut dreg with a high nutritional content.